Tetanus neurotoxin HCC protein commits T cells to IFN-Î³ producing cells - Torabi Goudarzi, S; hajivalili, M; Hosseini, M; Ghafari Khamene, M; Yazdani, Y; Sadreddini, S; Miahipour, A; Younesi, V; Yousefi, M (Cellular and Molecular Biology, 2016)
A protective response against tetanus toxin and toxoid demands efficient specific T cell and B cell responses. Tetanus neurotoxin (TeNT), a 150 kDa polypeptide, is the main cause of tetanus disease. TeNT consists of two structurally distinct chains, a 50 kDa N-terminal light (L) and a 100 kDa C-terminal heavy (H) chain. C-terminal heavy (H) chain (fragment C) has two sub-domains named as proximal HCN and carboxy sub-domain or HCC. Beside neural binding property, HCC has been recently found as an immunodominant module of TeNT. In the present study, we investigated the effects of recombinant HCC (rHCC) on the expression of lineage specific transcription factors and secretion of a panel of functional cytokines including IFN-Î³, IL-4, and IL-17 from purified human T cells. Our results revealed that T-bet transcript level, as TH1 specific transcription factor, was significantly increased in the cells treated with 10 and 20 µg/ml of rHCC following 48 h treatment(p<0.05). Treated purified human T cells with rHCC showed significant increase in IFN-Î³ mRNA level and cytokine secretion, but not IL-4 and IL-17, following 48 h treatment. In conclusion, our results showed that treatment of T cells with r HCC resulted in development of Th1 lineage phenotype, which might lead to a specific and protective antibody mediated response against tetanus toxin.